Performance investigation of R32 and R410a refrigerants with different compressor lubricants - Ismail, Mohd. Farid; Wan Hamzah, Wan Azmi (2023)
The present study aims to investigate the effect of changing air condi- tioning refrigerants and compressor lubricants on system performance. Two types of